2014
DOI: 10.1055/s-0034-1372459
|View full text |Cite|
|
Sign up to set email alerts
|

One-Trocar–Assisted Pyeloplasty in Children: An 8-Year Single Institution Experience

Abstract: OTAP is safe, feasible, and efficacious. Operative times are similar or even shorter than those of other minimally invasive techniques and complication rate agrees with the findings of literature. OTAP can be considered a reasonable alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We have already demonstrated this technique to be feasible in terms of efficacy and safety in the first 90 days of life [10]. OTAP puts together the advantages of minimally invasive surgery and traditional dismembered pyeloplasty by Anderson-Hynes, and is therefore an excellent option for treating this category of patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already demonstrated this technique to be feasible in terms of efficacy and safety in the first 90 days of life [10]. OTAP puts together the advantages of minimally invasive surgery and traditional dismembered pyeloplasty by Anderson-Hynes, and is therefore an excellent option for treating this category of patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, in our institution, the preferred approach for hydronephrosis in children younger than 2 years has been the one-trocar-assisted pyeloplasty (OTAP) [8,9]. This procedure combines the advantages of a minimally invasive technique with the high success rate of standard dismembered pyeloplasty; it had already been proven to be a feasible technique in terms of efficacy and safety in patients treated in the first 90 days of life [10].…”
Section: Introductionmentioning
confidence: 99%
“…discussed the results of this technique in a retrospective review of 88 patients; they concluded that OTAP was safe, feasible and efficacious, with a success and complication rate similar to the open technique. [ 15 ] In 2010, Caione et al . reported a comparative study between open and one trocar retroperitoneal-assisted pyeloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other surgical techniques needed to be mentioned since they have been investigated in a similar setting with favorable outcomes and in particular one-trocar-assisted pyeloplasty (OTAP) and open pyeloplasty via mini-flank incision (9,10). Which are the patient-related benefits provided by RALP over these approaches?…”
Section: A Commentary Onmentioning
confidence: 99%